Effect of Exercise Prior to Sedentary Behavior on Vascular Health Parameters: A Systematic Review and Meta-Analysis of Crossover Trials - Francisco Javier Soto-Rodríguez; Alicia Peris Moya; Carolina Javiera Bobadilla-Agouborde; José Manuel Pérez-Mármol (SpringerOpen, 2024)
Abstract Background Sedentary behavior has been shown to negatively affect parameters of endothelial function and central hemodynamics, both of which are closely associated with vascular health. Exercise prior to sedentary behavior has demonstrated potential as a preventive strategy to mitigate these detrimental effects. To evaluate the impact of exercise prior to sedentary behavior on vascular health parameters in the adult population, a systematic review and meta-analysis were conducted, synthesizing the available body of knowledge. Methods A literature search was carried out in 6 databases. For each outcome, standard error and mean difference or standardized mean difference were calculated, as appropriate. An analysis was performed using a random effects model with a 95% confidence interval, using the inverse variance statistical method. Risk of bias assessment was performed using ROB2 and considerations for crossover trials. The quality of evidence was assessed using the GRADE system. Results Exercise performed prior to prolonged sedentary behavior resulted in increased flow-mediated vasodilation at the first and third hours of sedentary time, compared with the control condition of sedentary behavior without prior exercise [MD: 1.51% (95% CI: 0.57 to 2.45) and MD: 1.36% (95% CI: 0.56 to 2.16), respectively]. Moreover, prior exercise led to increased shear rate at the first and third hours of sedentary time [MD: 7.70 s^−1 (95% CI: 0.79 to 14.61) and MD: 5.21 s^−1 (95% CI: 1.77 to 8.43), respectively]. Furthermore, it increased blood flow at the third hour [SMD: 0.40 (95%CI: 0.07 to 0.72)], compared with the control condition of prolonged sedentary behavior without prior exercise. Regarding hemodynamic parameters, exercise prior to prolonged sedentary behavior decreased mean arterial pressure during the first and third hours of sedentary behavior [MD: -1.94 mmHg (95% CI: -2.77 to -1.11) and MD: -1.90 mmHg (95% CI: -3.27 to -0.53), respectively], and an increase in heart rate during the first hour [MD: 4.38 beats per minute (95%CI: 2.78 to 5.98)] compared with the control condition of prolonged sedentary behavior without prior exercise. Conclusions The findings of this research suggest that prior exercise may prevent the impairment of vascular health parameters caused by sedentary behavior. However, the quality of the evidence was estimated as moderate. Therefore, further experimental studies and high-quality clinical trials are needed in this field to strengthen the results and conclusions drawn. PROSPERO registration number CRD42023393686.